A constituição da persona satírica na obra de Juvenal - Cordeiro, Iana Lima (2019)
Our dissertation analyzes the construction of the ethos of the poetic persona in Roman satirist Juvenal’s Satires. Because of the scarcity of empirical biographical information about this author’s life, along with the perception of a tone oscillation throughout his texts, there has been some dissent among the scholars who have studied his work. From the understanding of the historical context in which the poet lived and the observance of satire’s literary characteristics, visible not only in Juvenal’s poetry but also in that of his predecessors’, we discuss two great perspectives among his critics: the biographical reading and the adoption of a poetic persona as an analytical tool – and, intrinsically connected to both, the perceivable tone variance that exists in his work. The result to our own reading of the Satires, along with our weighing of the different arguments on the matter presented to us by several authors, is that there is, in Juvenal’s work, a constructed ethos so solid and cohesive that our statement on the matter is that there is only one poetic persona in his work and the tone variance should not be considered more relevant than the recurring themes in his Satires. Thus, our analysis of what aspects compose the satirical voice is based on the consistent statements he displays throughout his work about certain themes. Our results are organized in four categories: a) the satire’s poet; b) condemnation of wealth; c) about women and d) decaying of society. We conclude, therefore, that this satirist constructs his ethos as a Roman citizen whose only alternative, as an expression to his indignation towards his contemporaries’ vicious behavior, is writing satires, and who also perceives this moral corruption as both the cause and the consequence of an irreversible social decadency.